A qualitative assessment of parental experiences with false‐positive newborn screening for Krabbe disease. Issue 1 (15th July 2021) - Peterson, Laiken; Siemon, Amy; Olewiler, Leah; McBride, Kim L.; Allain, Dawn C.
Abstract: Numerous US states have implemented newborn screening for Krabbe disease (Krabbe NBS) as a result of legislative state mandates. While healthcare provider opinions toward Krabbe NBS have been documented, few studies have explored parental experiences and opinions regarding Krabbe NBS. Eleven families, who received a false‐positive Krabbe NBS result and received genetic counseling at an institution in central Ohio, were consented to participate in semistructured interviews. Interviews explored parents' experiences throughout the NBS process and ascertained their opinions regarding Krabbe NBS. Three major themes emerged from thematic analysis: (1) improved understanding of the NBS process from a parent perspective, (2) the role of healthcare provider communication, and (3) the value of Krabbe NBS. Parents saw value in Krabbe NBS, despite many disclosing emotional distress and uncertainty throughout the NBS process. Parent experiences throughout the NBS process varied widely. Due to the expressed emotional distress, further research assessing effective communication during the NBS process is warranted. The researchers suggest additional NBS education for non‐genetics healthcare providers (i.e., nurses or primary care physicians) and further participation of genetic counselors in the NBS process may benefit families with a positive Krabbe NBS result.